High-permeability covalent organic framework composite nanofiltration membrane as well as preparation method and application thereof
By carrying out Schiff base reaction between amine compounds and aldehyde compounds at room temperature, and using vacuum suction filtration self-assembly technology, a highly permeable covalent organic framework composite membrane was prepared, solving the complex preparation conditions and processable in traditional methods. The problem of poor performance has achieved efficient separation of plant active drugs and dyes, with good acid and alkali resistance and high interception.
Patent Information
- Application Number
- CN202411689752.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-17
AI Technical Summary
The preparation conditions of traditional covalent organic skeleton composite films are complex and require high temperatures, and the processability of polycrystalline two-dimensional COF powders are poor, which limits its application in the field of membrane separation.
The highly permeable covalent organic skeleton composite nanofiltration membrane was prepared by the 'reaction-separation-assembly' method. The Schiff base reaction was carried out at room temperature by amine compounds and aldehyde compounds to obtain a COF suspension and self-assembled by vacuum suction filtration. Strategy is assembled on the hydrolyzed polyacrylonitrile support membrane to form a highly permeable covalent organic framework composite membrane.
The prepared highly permeable covalent organic skeleton composite membrane exhibits high retention rate and good acid and alkali resistance in the separation of plant active drugs and dyes. It is suitable for industrial-scale low-energy-consuming drug ingredient extraction and high environmental protection separation technology.
Smart Images

Figure CN119318889A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of extraction and separation of plant active drug components, and particularly relates to a high-permeability covalent organic skeleton composite nanofiltration membrane and a preparation method and application thereof. Background Art
[0002] Phytogenic drugs are active ingredients extracted from plants with unique pharmacological and biological activities. They play an important role in disease treatment and are widely used in the fields of anticancer and antitumor. At present, the separation and purification of active ingredients of phytogenic drugs are mainly based on column chromatography techniques such as macroporous resins and liquid chromatography. This technology has problems such as high operating pressure, long time consumption, and frequent use of large amounts of organic solvents in the separation process, which limits the development and utilization of plant-derived drugs. With the development of economy and society, the scale of industrial construction continues to expand, and the demand for low-energy consumption drug component extraction and purification and high environmental protection separation technology is also increasing. Membrane separation technology can better meet this demand than traditional separation processes. Membrane-based separation technology has a wide range of applications. Covalent organic frameworks (COFs) are a class of porous crystalline materials connected by covalent bonds. They have the advantages of high porosity, customizable properties, and high specific surface area. They have become a promising membrane material for molecular separation. Despite such prospects, the polycrystalline two-dimensional COF powders prepared by traditional methods have poor processability, which limits the application of COFs in membrane separation.
[0003] Patent CN 117959962 A discloses an ultra-high flux covalent organic framework composite nanofiltration membrane and its preparation method, comprising a porous membrane substrate and a selective separation layer of a cap-like nano-protrusion structure grown on the pores of the porous base membrane by gas-liquid interface polymerization; the covalent organic framework material is an imine-type two-dimensional layered covalent organic framework material structure. An aqueous phase containing aldehyde monomers is used to construct the liquid surface required for the interfacial polymerization reaction on the surface of the porous base membrane, and the amino monomers below the membrane are rapidly sublimated under heating conditions, and the rising amino small molecule organic matter undergoes Schiff base condensation reaction with the aldehyde small molecule organic matter in the droplets on the membrane surface. After a period of reaction, an ultra-high flux covalent organic framework composite membrane is obtained. The composite membrane prepared by the prior art has a high interception rate for a variety of dye molecules in water and an ultra-high permeation flux, but the preparation conditions for the covalent organic framework composite membrane are complicated and need to be carried out at high temperature. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high permeability covalent organic skeleton composite nanofiltration membrane and its application, so as to solve the problems existing in the above-mentioned prior art. The present invention adopts a "reaction-separation-assembly" method to prepare a high permeability covalent organic skeleton composite nanofiltration membrane, and the prepared composite membrane consists of a COFs active layer and a support layer. The high permeability covalent organic skeleton composite nanofiltration membrane prepared by the present invention has important application value in the separation of plant active drugs and dyes.
[0005] One of the technical solutions provided by the present invention:
[0006] A method for preparing a high-permeability covalent organic skeleton composite nanofiltration membrane comprises the following steps: adding an amine compound and an aldehyde compound to an organic solvent to generate a Schiff base reaction, allowing the mixture to stand at room temperature to obtain a COF suspension, assembling a diluted aqueous solution of the COF suspension on a hydrolyzed polyacrylonitrile support membrane through a vacuum filtration self-assembly strategy, and drying the mixture to obtain the high-permeability covalent organic skeleton composite nanofiltration membrane.
[0007] Preferably, the molar ratio of the amine compound to the aldehyde compound is (0.2-1.8):0.3.
[0008] Preferably, the amine compound is selected from TAPA (tris(4-aminophenyl)amine), TGCl (triaminoguanidine) or AZO (para-diaminoazobenzene), and the aldehyde compound is selected from GA (glutaraldehyde), GL (glyoxal) or MA (malondialdehyde).
[0009] Preferably, the preparation method of the hydrolyzed polyacrylonitrile support membrane is: polyacrylonitrile, polyvinyl pyrrolidone and an organic solvent are mixed at room temperature, stirred evenly to form a casting liquid, the casting liquid is scraped on a non-woven fabric, and a polyacrylonitrile membrane is prepared by a non-solvent phase conversion method, the polyacrylonitrile membrane is placed in an alkaline aqueous solution for hydrolysis reaction, washed with deionized water until neutral, and dried at room temperature to obtain the hydrolyzed polyacrylonitrile support membrane.
[0010] Preferably, the pore size of the non-woven fabric is 100 to 300 μm. The ratio of the casting solution to the non-woven fabric is 64 cm 2 -100 cm 2 Apply 2mL-3mL of casting solution on the non-woven fabric area.
[0011] More preferably, the mass ratio of polyacrylonitrile to polyvinyl pyrrolidone is (10-25):(3-18).
[0012] More preferably, the hydrolysis reaction temperature is 40-60° C. and the time is 1-2 h.
[0013] Preferably, in the diluted aqueous solution of the COF suspension, the COF suspension accounts for 12%-20% of the volume of the diluted aqueous solution. More preferably, in the diluted aqueous solution of the COF suspension, the COF suspension accounts for 12% of the volume of the diluted aqueous solution.
[0014] The invention provides a method for preparing a high-permeability covalent organic skeleton composite nanofiltration membrane. The precursor solution of the covalent organic skeleton composite membrane is prepared by completely dissolving an amine compound (TAPA, TGCl or AZO) and a flexible aldehyde compound (GA, GL or MA) in 5 mL of a dimethyl sulfoxide solvent, then uniformly mixing the mixture to produce a Schiff base reaction, and standing at room temperature for 24 hours to obtain a uniformly dispersed COF suspension.
[0015] The hydrolyzed polyacrylonitrile support membrane used as a base membrane is prepared by mixing and stirring three components of polyacrylonitrile, polyvinyl pyrrolidone and NN dimethylformamide to form a uniform casting liquid, and then the obtained casting liquid is scraped onto a non-woven fabric to form a polyacrylonitrile membrane through a non-solvent phase conversion method; the polyacrylonitrile membrane is then placed in a 1.5-2.5M sodium hydroxide aqueous solution at 40-60°C for heat treatment for 1-2 hours to hydrolyze to obtain a carboxyl-rich hydrolyzed polyacrylonitrile support membrane, and a covalent organic skeleton active layer is assembled on the surface of the hydrolyzed polyacrylonitrile support membrane through vacuum-assisted self-assembly.
[0016] The second technical solution provided by the present invention is:
[0017] A high-permeability covalent organic skeleton composite nanofiltration membrane prepared by the above preparation method.
[0018] The third technical solution provided by the present invention is:
[0019] An application of the above-mentioned high-permeability covalent organic skeleton composite nanofiltration membrane in separating dyes, wherein the dyes include one or more of indigo, methylene blue, methyl orange, crystal violet, chrome black T, betalain, acid fuchsin, Congo red, methyl blue and benghalensis.
[0020] The fourth technical solution provided by the present invention is:
[0021] An application of the above-mentioned high-permeability covalent organic skeleton composite nanofiltration membrane in separating plant active drug molecules, wherein the plant active drugs include one or more of protocatechuic acid, chlorogenic acid, loganin, eleutheroside E, vinblastine, vincristine and vinblastine sulfate.
[0022] The technical principle of the present invention is as follows: the present invention prepares a high-permeability covalent organic skeleton composite nanofiltration membrane by vacuum filtration of a COF suspension, firstly, completely dissolving an amine compound and an aldehyde compound in a dimethyl sulfoxide solvent respectively and then uniformly mixing them to cause a Schiff base reaction, and then standing at room temperature to obtain a uniformly dispersed COF suspension, and then assembling the COF suspension on a hydrolyzed polyacrylonitrile support membrane through a simple vacuum-assisted self-assembly strategy, and then covering the surface of the hydrolyzed polyacrylonitrile support membrane with a synthesized imine covalent organic network, and the unreacted amino group and the carboxyl group on the hydrolyzed polyacrylonitrile support layer through electrostatic interaction so that the covalent organic skeleton active layer and the hydrolyzed polyacrylonitrile support layer are tightly combined, thereby modifying the hydrolyzed polyacrylonitrile, achieving the effect of changing its surface physical and chemical properties, and avoiding the problem of decreased membrane performance caused by unstable membrane layer and separation from the support layer in actual applications.
[0023] Compared with the prior art, the present invention has the following advantages and technical effects:
[0024] The present invention aims to solve the problem of the difficulty in processing traditional COF and the difficulty in preparing high-performance COF membranes. The COF composite membrane prepared by this method has certain application value in the separation and purification of active drugs.
[0025] The high permeability covalent organic skeleton composite nanofiltration membrane prepared by the present invention is mainly used for separation of plant active drugs, and the permeation flux is as high as 100L·m -2 ·h -1 bar -1 , showing a high retention rate for plant active drugs of different molecular weights. In addition, the prepared high permeability covalent organic skeleton composite nanofiltration membrane also achieved a high retention rate for dye molecules, which can reach 97%. Because the composite nanofiltration membrane has a hydrophilic, highly smooth surface and good acid and alkali resistance, after being soaked in 4mol / L hydrochloric acid for 30 days, the retention rate of the membrane for red bengal dye is still greater than 97%. In addition, after being soaked in 6mol / L sodium hydroxide for 24 hours, the retention rate of the membrane for red bengal dye remains at 97%. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0027] Figure 1 (a) is the infrared spectra of GA, TAPA and TAPA-GA / HPAN-3 in Example 1, Figure 1(b) is a graph showing the pore size of an independent TAPA-GA / HPAN-3 membrane tested in this example;
[0028] Figure 2 (a) is a surface scanning electron microscope image of the high permeability covalent organic framework composite nanofiltration membrane prepared in Example 1, (b) is a cross-sectional scanning electron microscope image, and (c) is an atomic force microscope image;
[0029] Figure 3 The separation performance influence curves of the high permeability covalent organic framework composite nanofiltration membranes prepared in Examples 1-3 and Comparative Examples 1-2;
[0030] Figure 4 (a) is a bar graph showing the separation performance of the high permeability covalent organic framework composite nanofiltration membrane prepared in Example 1 for different dyes, and (b) is a bar graph showing the separation performance of different plant active drug molecules;
[0031] Figure 5 (a) is a bar graph showing the retention effect of the high permeability covalent organic framework composite nanofiltration membrane prepared in Example 1 on bengalensis under different operating pressures, (b) is a bar graph showing the long-term separation performance of the high permeability covalent organic framework composite nanofiltration membrane prepared in Example 1 on bengalensis, (c) is a bar graph showing the retention effect of bengalensis after immersion in different hydrochloric acid concentrations and for different times, and (d) is a bar graph showing the retention effect of bengalensis after immersion in different sodium hydroxide concentrations. DETAILED DESCRIPTION
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] The room temperature in the present invention refers to 25±2°C.
[0038] It should be noted that, unless otherwise specified, % in Examples and Comparative Examples is based on mass.
[0039] The raw materials required in the embodiments of the present invention are all purchased from commercial sources.
[0040] The cross-flow filtration devices used in the separation tests in the embodiments of the present invention all used small membrane flat plate test machines (TYLG-17) purchased from Shandong Bona Group.
[0041] In the embodiment of the present invention, TAPA (1,3,5-tris (4-aminophenyl) benzene) and GA (glutaraldehyde) are used as raw materials to prepare a COF suspension. The specific preparation process is as follows: first, TAPA (0.2-1.8 mmol) and GA (0.3 mmol) are respectively dissolved in 5 mL of dimethyl sulfoxide solution, mixed to obtain a uniform solution, and then the two prepared uniform solutions are mixed, and the mixed solution is allowed to stand at room temperature for 24 hours to obtain a COF suspension (TAPA-GACOF), and the reaction formula is as follows:
[0042]
[0043] In the embodiment of the present invention, TAPA (1,3,5-tris(4-aminophenyl)benzene) and GL (glyoxal) are used as raw materials to prepare a COF suspension. The specific preparation process is as follows: first, TAPA (0.2-1.8 mmol) and GL (0.3 mmol) are respectively dissolved in 5 mL of dimethyl sulfoxide solution, mixed to obtain a uniform solution, and then the two prepared uniform solutions are mixed, and the mixed solution is allowed to stand at room temperature for 24 hours to obtain a COF suspension (TAPA-GL COF). The reaction formula is as follows:
[0044]
[0045] In the embodiment of the present invention, TAPA (1,3,5-tris(4-aminophenyl)benzene) and MA (malondialdehyde) are used as raw materials to prepare a COF suspension. The specific preparation process is as follows: first, TAPA (0.2-1.8 mmol) and MA (0.3 mmol) are respectively dissolved in 5 mL of dimethyl sulfoxide solution, mixed to obtain a uniform solution, and then the two prepared uniform solutions are mixed, and the mixed solution is allowed to stand at room temperature for 24 hours to obtain a COF suspension (TAPA-MA COF). The reaction formula is as follows:
[0046]
[0047] In the embodiment of the present invention, triaminoguanidine hydrochloride and GA (glutaraldehyde) are used as raw materials to prepare a COF suspension. The specific preparation process is as follows: first, triaminoguanidine hydrochloride (0.2-1.8 mmol) and GA (0.3 mmol) are respectively dissolved in 5 mL of dimethyl sulfoxide solution, mixed to obtain a uniform solution, and then the two prepared uniform solutions are mixed, and the mixed solution is allowed to stand at room temperature for 24 hours to obtain a COF suspension (TGCl-GACOF), and the reaction formula is as follows:
[0048]
[0049] In the embodiment of the present invention, AZO (diaminoazobenzene) and GA (glutaraldehyde) are used as raw materials to prepare a COF suspension. The specific preparation process is as follows: first, AZO (0.2-1.8 mmol) and GA (0.3 mmol) are respectively dissolved in 5 mL of dimethyl sulfoxide solution, and mixed to obtain a uniform solution. Then, the two prepared uniform solutions are mixed, and the mixed solution is allowed to stand at room temperature for 24 hours to obtain a COF suspension (AZO-GACOF). The reaction formula is as follows:
[0050]
[0051] The method for preparing the hydrolyzed polyacrylonitrile support membrane in the embodiment of the present invention is as follows:
[0052] 1) Preparation of polyacrylonitrile support membrane: 10-25wt% polyacrylonitrile, 3-18wt% polyvinyl pyrrolidone and dimethylformamide are mixed at room temperature; magnetic stirring is performed until the reaction solution is light yellow, uniform, transparent and viscous, and then it is allowed to stand at room temperature until all bubbles disappear, and the obtained casting solution is scraped onto a non-woven fabric board with a pore size of 100-300μm with a glass rod, and then immersed in 20-30℃ deionized water after 15-30s, and the deionized water is replaced every 6-10h, and a polyacrylonitrile membrane is obtained after 20-30h;
[0053] 2) Soak the polyacrylonitrile membrane obtained in step 1) in a 1.5-2.5M sodium hydroxide aqueous solution and heat treat it at 40-60°C for 1-2h. After the reaction is completed, wash it with deionized water until the washing water is neutral, and dry it naturally at room temperature to obtain a hydrolyzed polyacrylonitrile support membrane. Put the hydrolyzed polyacrylonitrile membrane into deionized water for subsequent use.
[0054] In the embodiment of the present invention, the COF suspension is assembled on a hydrolyzed polyacrylonitrile support membrane by a vacuum filtration self-assembly strategy to prepare the high permeability covalent organic framework composite nanofiltration membrane. The specific operation is as follows: a certain volume of COF suspension is diluted with water to 25 mL to obtain a uniform dilution, and the dilution is then filtered onto a hydrolyzed polyacrylonitrile substrate by a vacuum assisted self-assembly method to obtain a covalent organic framework composite membrane, the composite membrane is placed in a 60°C oven, heat treated for 10 minutes, and the obtained high permeability covalent organic framework composite nanofiltration membrane is placed in deionized water for subsequent use.
[0055] Example 1 A method for preparing a high permeability covalent organic skeleton composite nanofiltration membrane
[0056] 1) 1.5 g (11 wt%) polyacrylonitrile, 0.546 g (4 wt%) polyvinyl pyrrolidone and 12.23 mL (85 wt%) dimethylformamide were added to a glass vial and stirred with a magnetic stirrer until the liquid in the vial was light yellow, transparent and viscous; then the mixture was allowed to stand at room temperature until no bubbles were present, and 1.5 mL of the obtained casting solution was scraped onto a non-woven fabric plate (64 cm) with a gap of 200 μm. 2 ), and then immediately immersed in 25°C deionized water after staying in the air for 20s, and then the water was changed every 8h to obtain a polyacrylonitrile membrane after 24h; the polyacrylonitrile membrane was immersed in 2mol / L sodium hydroxide solution and heat-treated at 50°C for 1h, and then the polyacrylonitrile membrane was washed with deionized water until the rinsed water was neutral, and the hydrolyzed polyacrylonitrile support membrane was dried at room temperature, recorded as HPAN, and stored in deionized water for subsequent use;
[0057] 2) First, 0.2 mmol of TAPA and 0.3 mmol of GA were dissolved in 5 mL of dimethyl sulfoxide solution respectively, and then the two prepared uniform solutions were mixed. Finally, the mixed solution was allowed to stand at room temperature for 24 h to obtain a COF suspension (TAPA-GA COF). 3 mL of the TAPA-GA COF suspension was diluted to 25 mL with water, and then the diluted aqueous solution of the COF suspension was assembled on the HPAN prepared in step 1) by a simple vacuum filtration self-assembly strategy (the vacuum pump source was from Yuhua brand circulating water vacuum pump, model SHZ-DⅢ, speed was 2800 rpm, power was 370 W, voltage was 220 V, and the vacuum degree was maintained at -0.08 to -0.1 MPa during this process). The membrane was heat treated in an oven at 60°C for 10 min to obtain a high permeability covalent organic skeleton composite nanofiltration membrane, recorded as TAPA-GA / HPAN-3, and the prepared composite nanofiltration membrane was placed in ionized water for subsequent use.
[0058] Figure 1 (a) is the infrared spectra of GA, TAPA and TAPA-GA / HPAN-3 in Example 1. It can be seen that the TAPA-GA / HPAN covalent organic skeleton membrane has a wavelength of 1650 cm -1 The strong -C=N-stretching vibration was shown at , indicating that the reaction between the aldehyde group and the amine group occurred successfully; Figure 1 (b) is a graph showing the pore size of an independent TAPA-GA / HPAN-3 membrane tested in this example, which is 1.78 nm.
[0059] Figure 2 (a) is a surface scanning electron micrograph of the high permeability covalent organic framework composite nanofiltration membrane prepared in Example 1, (b) is a cross-sectional scanning electron micrograph, and (c) is an atomic force micrograph. Figure 2 It can be seen that the covalent organic skeleton active layer completely covers the surface of the support membrane, forming a dense support layer. Through the test of the membrane cross section, it can be clearly observed that the thickness of the selective layer is about 26μm. The atomic force microscope tested the smoothness of the membrane surface and it can be observed that the membrane surface is relatively smooth with a roughness of 4.45nm.
[0060] Example 2 A method for preparing a high permeability covalent organic framework composite nanofiltration membrane
[0061] The same as Example 1, except that in step 2), 4 mL of TAPA-GA COF suspension was diluted with water to 25 mL, and then the diluted aqueous solution of the COF suspension was assembled on the HPAN prepared in step 1) by a simple vacuum filtration self-assembly strategy, and the membrane was heat-treated in an oven at 60° C. for 10 min to obtain a high permeability covalent organic framework composite nanofiltration membrane, which was recorded as TAPA-GA / HPAN-4.
[0062] Example 3 Preparation method of a high permeability covalent organic skeleton composite nanofiltration membrane
[0063] The same as Example 1, except that in step 2), 5 mL of TAPA-GACOF suspension was diluted with water to 25 mL, and then the diluted aqueous solution of the COF suspension was assembled on the HPAN prepared in step 1) by a simple vacuum filtration self-assembly strategy, and the membrane was heat treated in an oven at 60°C for 10 min to obtain a high permeability covalent organic skeleton composite nanofiltration membrane, which was recorded as TAPA-GA / HPAN-5.
[0064] Example 4 Preparation method of a high permeability covalent organic skeleton composite nanofiltration membrane
[0065] Same as Example 1, except that the glutaraldehyde in step 2) is replaced by glyoxal.
[0066] Example 5 A method for preparing a high permeability covalent organic framework composite nanofiltration membrane
[0067] Same as Example 1, except that the glutaraldehyde in step 2) is replaced by malondialdehyde.
[0068] Comparative Example 1 Preparation method of a high permeability covalent organic skeleton composite nanofiltration membrane
[0069] The same as Example 1, except that in step 2), 1 mL of TAPA-GA COF suspension was diluted with water to 25 mL, and then the diluted aqueous solution of the COF suspension was assembled on the HPAN prepared in step 1) by a simple vacuum filtration self-assembly strategy, and the membrane was heat-treated in an oven at 60° C. for 10 min to obtain a high permeability covalent organic framework composite nanofiltration membrane, which was recorded as TAPA-GA / HPAN-1.
[0070] Comparative Example 2 Preparation method of a high permeability covalent organic skeleton composite nanofiltration membrane
[0071] The same as Example 1, except that in step 2), 2 mL of TAPA-GA COF suspension was diluted with water to 25 mL, and then the diluted aqueous solution of the COF suspension was assembled on the HPAN prepared in step 1) by a simple vacuum filtration self-assembly strategy, and the membrane was heat-treated in an oven at 60° C. for 10 min to obtain a high permeability covalent organic framework composite nanofiltration membrane, which was recorded as TAPA-GA / HPAN-2.
[0072] Performance test 1
[0073] The separation performance of the high permeability covalent organic framework composite nanofiltration membranes prepared in Examples 1-3 and Comparative Examples 1-2 was measured by a 5 mg / L benghalensis aqueous solution through a circulating cross-flow filtration method. Figure 3 The separation performance influence curves of the high permeability covalent organic framework composite nanofiltration membranes prepared in Examples 1-3 and Comparative Examples 1-2 are shown in FIG. Figure 3 It can be seen that when the TAPA-GA COF loading is too low (1-2 mL loading in Comparative Examples 1 and 2), the formed membrane is discontinuous and has defects, so the water flux is very large (261.57 L·m -2 ·h -1 bar -1 , corresponding to the case where the TAPA-GA loading amount is 1 mL; when the loading amount is 2 mL, the water flux is 198.73 L·m -2 ·h -1 bar -1 ), the retention rate of bengalensis is relatively low (91.94%, corresponding to the case of TAPA-GA loading of 1 mL; when the loading is 2 mL, the retention rate is 94.25%); when the TAPA-GA COF loading is too high (Examples 1-3, loading 3-5 mL), because the COF content for Schiff base reaction is limited, the retention rate of the membrane for dye remains unchanged (when the loading is 3 mL, the retention rate is 97.99%; when the loading is 4 mL, the retention rate is 97.81%; when the loading is 5 mL, the retention rate is 97.84%), but with the increase of TAPA-GA COF loading, the mass transfer resistance increases, so the water flux continues to decrease (when the loading is 3 mL, the water flux is 105.10 L·m -2 ·h -1 bar -1 ; When the loading amount is 4 mL, the water flux is 95.54 L·m -2 ·h -1 bar -1 ; When the loading volume is 5 mL, the retention rate is 85.30 L·m -2 ·h -1 bar -1 ), so the optimal addition amount is 3 mL of TAPA-GACOF in Example 1.
[0074] Separation performance test of dyes and plant active pharmaceutical ingredients
[0075] The high permeability covalent organic framework composite nanofiltration membrane prepared in Example 1 was used, and a cross-flow filtration device was used to measure the separation performance of the membrane at a pressure of 2 bar using 5 mg / L dyes (indigo, methylene blue, methyl orange, crystal violet, chrome black T, betaine, acid fuchsin, Congo red, methyl blue and tiger red) or 5 g / L plant drug molecules (protocatechuic acid, chlorogenic acid, loganin, eleutheroside E, vinblastine, vincristine and vinblastine sulfate) as feeds.
[0076] Figure 4 (a) is a bar graph showing the separation performance of the high permeability covalent organic framework composite nanofiltration membrane prepared in Example 1 for different dyes, and (b) is a bar graph showing the separation performance of different plant active drug molecules. Figure 4 As shown in (a), due to the small pore size of the composite membrane (1.78 nm), it can retain dyes of different molecular weights, such as Congo red (696.66 Da, The retention rate is 99.38%) and acid blue (799.80Da, The retention rate is 97.50%). For small molecular weight dyes such as methyl orange ( negatively charged), although the molecular size is less than 1.78nm, the retention rate of TAPA-GA / HPAN-3 for methyl orange is 98.66%. From the above results, it can be seen that the high permeability covalent organic skeleton composite nanofiltration membrane prepared in Example 1 of the present invention retains dyes of different molecular weights through Donan effect and molecular sieving.
[0077] Figure 4 As shown in (b), seven active pharmaceutical ingredients (protocatechuic acid, chlorogenic acid, loganin, eleutheroside E, vinblastine, vincristine and vinblastine sulfate) were selected as model molecules for the molecular separation experiment of plant active pharmaceutical ingredients. Figure 4 (a) and Figure 4 As shown in (b), TAPA-GA / HPAN-3 rejected all model molecules in the order of molecular size, indicating that size rejection plays a key role in the filtration process. TAPA-GA / HPAN-3 showed good rejection, such as 93.44% for vinblastine (810.99Da), 92.70% for vincristine (824.96Da), and 86.60% for vinblastine sulfate (909.05Da). It was observed that the molecular weight of vinblastine sulfate is larger than that of vincristine and vinblastine, but the retention rate of TAPA-GA / HPAN-3 is lower than that of the latter two. The above phenomenon is attributed to vinblastine sulfate. The molecular size is smaller than that of vinblastine and vincristine
[0079] Stability test
[0080] The high permeability covalent organic framework composite nanofiltration membrane prepared in Example 1 was used to perform stability performance test.
[0081] The retention effect of the membrane on bengal (5 g / L) was measured at different pressures. Figure 5 (a) is a bar graph showing the interception effect of the high permeability covalent organic framework composite nanofiltration membrane prepared in Example 1 on bengalensis at different operating pressures; Figure 5 As can be seen in (a), when the operating pressure increases from 1 bar to 10 bar, the retention rate of tiger red only fluctuates slightly.
[0082] The long-term stability test of the membrane was carried out at 2 bar pressure, and the retention effect of bengalensis was continuously tested. Figure 5 (b) is a bar chart showing the long-term separation performance of the high permeability covalent organic framework composite nanofiltration membrane prepared in Example 1 for bengalensis. Figure 5 As can be seen in (b), in the initial stage of the membrane operation at a pressure of 2 bar, the bengalen rejection rate is about 98% and the membrane flux is about 110 L·m -2 ·h -1 bar -1 After 18 h, the flux and bengalensis retention rate remained almost unchanged.
[0083] In order to further evaluate the stability of the membrane, the present invention also soaked the membrane in acid and alkali respectively. The separation performance of bengalensis was tested after soaking in 1mol / L, 2mol / L, and 4mol / L hydrochloric acid for 48h and in 4mol / L hydrochloric acid for 30 days, and the stability of the membrane was tested. Figure 5 (c) is a bar graph showing the retention effect of bengalensis at different hydrochloric acid concentrations and different soaking times; the separation performance of bengalensis was tested after soaking in 1mol / L, 2mol / L, 4mol / L, and 6mol / L sodium hydroxide solutions for 48h, and used to evaluate the stability of the membrane. Figure 5 (d) is a bar graph showing the interception effect of different sodium hydroxide concentrations on bengalensis. Figure 5 As shown in (c), the high permeability covalent organic skeleton composite nanofiltration membrane has basically unchanged retention rate for bengalensis after being immersed in 1mol / L, 2mol / L, 4mol / L hydrochloric acid for 48h and in 4mol / L hydrochloric acid for 30 days, and the water flux has increased by about 14%. This is because the acid immersion removes some unreacted monomers and oligomers, and the elimination of these obstacles opens up a more unobstructed mass transfer channel, thereby promoting solvent penetration and rejecting solutes. Figure 5As shown in (d), the retention rate of the composite nanofiltration membrane prepared in Example 1 for bengalensis remained basically unchanged after being immersed in 1 mol / L, 2 mol / L, 4 mol / L and 6 mol / L sodium hydroxide for 48 h, and the water flux decreased with the increase of the sodium hydroxide concentration (for example, the water flux after being immersed in 2 mol / L sodium hydroxide solution for 48 h was 61.87 L·m -2 ·h -1 bar -1 After immersion in 6 mol / L sodium hydroxide solution for 48 h, the water flux was 31.35 L·m -2 ·h -1 bar -1 This is because high concentration of sodium hydroxide crystallizes in the membrane pores, increasing the water transmission resistance and causing the composite membrane flux to decrease. The above test results all show that the composite membrane has good stability.
[0084] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a high permeability covalent organic framework composite nanofiltration membrane, characterized in that: Amine compounds and aldehyde compounds are added to an organic solvent to produce a Schiff base reaction, and the mixture is allowed to stand at room temperature to obtain a COF suspension. The diluted aqueous solution of the COF suspension is assembled on a hydrolyzed polyacrylonitrile support membrane through a vacuum filtration self-assembly strategy, and then dried to prepare the high-permeability covalent organic skeleton composite nanofiltration membrane.
2. The method for preparing a high permeability covalent organic framework composite nanofiltration membrane according to claim 1, characterized in that: The molar ratio of the amine compound to the aldehyde compound is (0.2-1.8):0.
3.
3. The method for preparing a high permeability covalent organic framework composite nanofiltration membrane according to claim 1, characterized in that: The amine compound is selected from tris(4-aminophenyl)amine, triaminoguanidine or p-diaminoazobenzene, and the aldehyde compound is selected from glutaraldehyde, glyoxal or malondialdehyde.
4. The method for preparing a high permeability covalent organic framework composite nanofiltration membrane according to claim 1, characterized in that: The preparation method of the hydrolyzed polyacrylonitrile support membrane is as follows: polyacrylonitrile, polyvinyl pyrrolidone and an organic solvent are mixed at room temperature, stirred evenly to prepare a casting liquid, the casting liquid is scraped on a non-woven fabric, a polyacrylonitrile membrane is prepared by a non-solvent phase conversion method, the polyacrylonitrile membrane is placed in an alkaline aqueous solution for hydrolysis reaction, washed with deionized water until neutral, and dried at room temperature to obtain the hydrolyzed polyacrylonitrile support membrane.
5. The method for preparing a high permeability covalent organic framework composite nanofiltration membrane according to claim 4, characterized in that: The mass ratio of polyacrylonitrile to polyvinyl pyrrolidone is (10-25): (3-18).
6. The method for preparing a high permeability covalent organic framework composite nanofiltration membrane according to claim 4, characterized in that: The temperature of the hydrolysis reaction is 40-60° C. and the time is 1-2 hours.
7. The method for preparing a high permeability covalent organic framework composite nanofiltration membrane according to claim 1, characterized in that: In the diluted aqueous solution of the COF suspension, the COF suspension accounts for 12%-20% of the volume of the diluted aqueous solution.
8. A high permeability covalent organic skeleton composite nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the high permeability covalent organic framework composite nanofiltration membrane according to claim 8 in separating dyes, characterized in that: The dye includes one or more of indigo, methylene blue, methyl orange, crystal violet, chrome black T, betalain, acid fuchsin, Congo red, methyl blue and benghalensis.
10. Use of the high permeability covalent organic framework composite nanofiltration membrane according to claim 8 in separating plant active drug molecules, characterized in that: The plant active drugs include one or more of protocatechuic acid, chlorogenic acid, loganin, eleutheroside E, vinblastine, vincristine and vinblastine sulfate.